Opportunities and Challenges of Halal Supervisor Training in the Development of the Halal Ecosystem - Wardani, Nur Rahmah; Sukirman, Dadang (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
After the Halal Product Guarantee Law in Indonesia was created, halal supervisors became one of the new jobs needed because they are important in developing the halal ecosystem. In 2023, more than four thousand halal certificates will be issued to those who have passed the training, but this is still very small compared to the number of business actors who have not been halal certified, which is even recorded as more than 15 million micro and small business actors. The important role of halal supervisors in the halal ecosystem is currently very much needed. The question is, what are the opportunities and challenges of the halal supervisor training in the development of the halal ecosystem? This research uses a qualitative phenomenological approach. As a result, opportunities for the halal supervisor training can be seen from the need for human resources in the halal ecosystem and career aboard. Meanwhile, the challenges faced are related to gain participant causes of public halal awareness, lack of information about halal supervisors, and the costs that must be spent on training halal supervisors.